Social Media in South India - Venkatraman, Shriram (Why We Post, 2017)
One of the first ethnographic studies to explore use of social media in the everyday lives of people in Tamil Nadu, Social Media in South India provides an understanding of this subject in a region experiencing rapid transformation. The influx of IT companies over the past decade into what was once a space dominated by agriculture has resulted in a complex juxtaposition between an evolving knowledge economy and the traditions of rural life. While certain class tensions have emerged in response to this juxtaposition, a study of social media in the region suggests that similarities have also transpired, observed most clearly in the blurring of boundaries between work and life for both the old residents and the new.